INCREASING STUDENTS' LEARNING MOTIVATION WITH SPIRITUAL GUIDANCE PROGRAM - Junaedi, Achmad; Suhartini, Titik (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The low learning outcomes of students are caused by a lack of student motivation in learning. This study aimed to determine the effect of spiritual guidance on students' learning motivation. This study uses a pre-experimental research design with a one-group pretest-posttest design method. The population is SMKN 1 Kraksaan students, with a sample of 40 Class X students who meet the inclusion criteria at SMKN 1 Kraksaan. The sampling technique used is stratified random sampling. The data analysis with the Kendal Tau test determines the influencing variable with a significance level of p 0.05. The research results on respondents' satisfaction before spiritual guidance were mostly moderate motivation (65%) and low motivation (35%). While learning motivation after spiritual guidance mostly comes from high inspiration (80%) and moderate motivation (20%). The results of the data analysis test obtained P = 0.000, so the conclusion is that there is an effect of spiritual guidance on students' learning motivation. The implications obtained from the program guidance carried out continuously by the teacher will impact student learning outcomes.